2022
DOI: 10.3390/jpm12060926
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Postpartum Sexual Dysfunction in Spanish Women: A Cross-Sectional Study

Abstract: (1) Background: Female sexual dysfunction (FSD) has a high prevalence globally, and perinatal factors favor FSD, especially in the postpartum period. The aim was to determine the prevalence and factors influencing FSD in the postpartum period; (2) Methods: An observational study carried out in three primary care centers in southern Spain, with women in the postpartum period who had a single low-risk birth. One hundred and seventeen women answered the Female Sexual Function questionnaire during the 4th month po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…The percentage of women with postpartum FSDs varies between 40% and 83% 39 40. A recent publication stated that 30.3% of nursing women did not get easily aroused, 20.2% of participants complained about difficult penetration and 14.4% of respondents could not reach orgasm 41. Banaei et al estimated that the prevalence of dyspareunia was 35% at 2 months postpartum and 22% at 6–12 months 42.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of women with postpartum FSDs varies between 40% and 83% 39 40. A recent publication stated that 30.3% of nursing women did not get easily aroused, 20.2% of participants complained about difficult penetration and 14.4% of respondents could not reach orgasm 41. Banaei et al estimated that the prevalence of dyspareunia was 35% at 2 months postpartum and 22% at 6–12 months 42.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from physiological reasons, culture and sociodemographics influence the decision of women to return to sexual activity 45 46. According to recent studies, 20–50% of women do not engage in intercourse before 3 months post partum 41 47. Breastfeeding mothers are less likely to resume sexual relations at early post partum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this study showed that participants who delivered their last child with tears/episiotomy and instrument were 3.7 (AOR = 3.72; 95% CI = 1.57, 8.80) and 7.0 (AOR = 7.04; 95% CI = 1.24, 39.8) times more likely to develop FSD as compared to those who delivered vaginally without tears/episiotomy respectively. Similarly, a study conducted on Spanish women showed the existence of a significant association between instrumental delivery and FSD [ 60 ]. Similarly, studies demonstrated that the association between instrumental delivery and FSD due to the increased risk of injuries that may occur with this type of intervention during delivery [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 97%
“…Penurunan hormon estrogen pada minggu pertama pasca persalinan mengakibatkan sekresi cairan pelumas vagina alamiah berkurang sehingga membuat rasa sakit saat berhubungan. Beberapa masalah yang dapat dialami saat melakukan hubungan seksual di masa nifas adalah: vagina yang mengering, jaringan vagina yang tipis, hilangnya elastisitas jaringan vagina, perineum yang sobek, perdarahan, nyeri, otot yang mengendur, letih dan libido yang rendah [8]- [11].…”
Section: Pendahuluanunclassified